Frederick E. Brenk on Plutarch, religious thinker and biographer : "The religious spirit of Plutarch of Chaironeia" and "The Life of Mark Antony" - Brenk, Frederick E. (Brill's Plutarch Studies, 2017)
The present book Frederick E. Brenk: Plutarch, Religious Thinker and Biographer, "The Religious Spirit of Plutarch of Chaironeia" and "The Life of Mark Antony" includes the updated and revised version of two seminal articles on Plutarch by F. E. Brenk published thirty years ago in ANRW. Edited by Lautaro Roig Lanzillotta, both articles cover the two sides of Plutarch's corpus, the Lives and Moralia .